Late Preterm Newborns: Breastfeeding and Complementary Feeding Practices - Ieva Dijokienė; Raminta Žemaitienė; Dalia Stonienė (MDPI AG, 2024)
Background: The aim of this study is to identify factors associated with successful breastfeeding in late preterm infants (LPIs) and explore the initiation of complementary feeding; Methods: Prospective cohort study was conducted of infants born at 34+0 to 36+6 weeks gestational age in the Hospital of the Lithuanian University of Health Sciences Kaunas Clinics during 2020-2021. Families were followed up until the infants reached 12 months of age. Average breastfeeding initial time, average breastfeeding duration time, prevalence of exclusive breastfeeding and average solid-food feeding initiation time were examined. The correlations among factors that might affect breastfeeding rates were calculated using the chi-square test (p < 0.05); Results: In our study with 222 eligible participants, we observed a statistically significant delay in breastfeeding initiation only in the 34+0+6 gestational age group (p < 0.001). At discharge, the 36+0+6 group exhibited a significantly higher exclusive breastfeeding rate (p < 0.001). Over the first year, breastfeeding rates varied, with no correlation found between duration of exclusive breastfeeding and gestational age. Initial solid-food feeding times were similar across groups, and all infants were introduced to vegetables first; Conclusions: Vaginal delivery, skin-to-skin contact after birth, early rooming-in, and breastfeeding within 2 h after birth statistically significantly causes earlier breastfeeding initiation and longer duration of breastfeeding in LPIs. All infants began solid-food feeding at an average age of 5 months, with vegetables being the primary food choice.